2002
DOI: 10.1142/s0217732302006710
|View full text |Cite
|
Sign up to set email alerts
|

Θ-Term AND COSMOLOGICAL CONSTANT FROM CJD ACTION

Abstract: In the gravity without metric formalism of Capovilla, Jacobson and Dell, the topological θ-term appears through a canonical transformation.The origin of this canonical transformation is probed here. It is shown here that when θ-term appears cosmological λ-term also appears simultaneously.PACS numbers : 04.20.Cv, 04.20.Fy Key words : Canonical transformation, Torsion, θ-term, Cosmological constant Einstein originally formulated the theory of gravitation as a set of differential equations obeyed by the metric te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…So this approach is very much akin to our present approach if we consider that torsion is connected to internal space which makes the spacetime noncommutative such that the gravitational constant fixes the scale of noncommutativity. This supports the findings of some other works, when the gauge group is SL(2, C) which is the covering group of SO (3,1), where torsion has been shown to be linked with CP-violation 27 and fermion mass 28 .…”
Section: Discussionsupporting
confidence: 91%
“…So this approach is very much akin to our present approach if we consider that torsion is connected to internal space which makes the spacetime noncommutative such that the gravitational constant fixes the scale of noncommutativity. This supports the findings of some other works, when the gauge group is SL(2, C) which is the covering group of SO (3,1), where torsion has been shown to be linked with CP-violation 27 and fermion mass 28 .…”
Section: Discussionsupporting
confidence: 91%
“…In this context we may mention a recent work [30] where, in the gravity without metric formalism of gravity, a particular canonical transformation of the field variables causes the simultaneous appearance of the CP-violating θ-term and the cosmological term. Here we also like to consider the finding of some other works, where the gauge group is SL(2, C) , where torsion has been shown to be linked with CP-violation [41] and fermion mass [42].…”
Section: Discussionmentioning
confidence: 99%
“…In some earlier works [29,30,15] φ has been treated as an inverse length constant. In a recent paper [16] φ has been associated, either in laboratory scale or in cosmic sale, with a local energy scale.…”
Section: Axial Vector Torsion and Gravitymentioning
confidence: 99%
“…It is important to note that, in our present formalism, the only assumption is that the torsion is represented by a null axial vector and the corresponding Lagrangian is a particular In a recent paper [45] it has been shown that, in the gravity without metric formalism of gravity, when one performs a particular canonical transformation of the field variables, CP-violating θ-term appears in the Lagrangian together with the cosmological term. This supports the finding of this note when we consider that the torsion, being an axial vector, has a certain role to play in CP-violation.…”
Section: Discussionmentioning
confidence: 99%